Nonlinear analysis of historic and contemporary vaulted masonry assemblages - O.A. Kamal (HBRC Journal, 2014)
This paper incorporates both analytical and experimental investigations of the nonlinear behavior of unreinforced masonry assemblages, especially curved elements such as arches, vaults and domes. The conservation of architectural and cultural heritage necessitates going through a comprehensive scientific procedure of assessment of unreinforced assemblages. Usually, linear analysis is conducted for simplifying analysis and design of masonry structures. However, such simplification might underestimate the structural capacity of these constructions in many cases, and thus the nonlinear analysis gives better description for the actual behavior and capacity of the structure. The present theoretical study utilizes finite element discretization, using a commercial nonlinear analysis computer program (ANSYS), which renders the approach easily and efficiently applicable by a practicing engineer. The adopted solution procedure is explained regarding material characterization and nonlinear solution parameters. Also, an experimental study was conducted in order to validate the accuracy of the adopted modeling and solution procedure by comparison with experimental results. Validation of the model was also ensured by means of comparison between the calculated numerical results and experimental results available in the literature. Further, the proposed modeling procedure was applied on existing historic and contemporary structures to demonstrate the ability of the proposed analysis to capture the behavior observed in real structures. Applications of the adopted procedure for design of new masonry constructions demonstrated the applicability of the proposed models in engineering practice. Finally, some conclusions and recommendations are presented.